Considerations about the evolutionary stasis of Notiolofos arquinotiensis (Mammalia: Sparnotheriodontidae), eocene of Seymour Island, Antarctica - Gelfo, Javier Nicolás (Ameghiniana)
Notiolofos arquinotiensis is the most abundant terrestrial placental mammal in the Paleogene of the Antarctic continent. Evidence suggests a South American origin of Sparnotheriodontidae, and an allopatric speciation event for the appearance of N. arquinotiensis. It was recorded exclusively on Seymour Island, through most of the La Meseta and Submeseta formations. Isotopic and paleomagnetic calibration of the units indicate a relatively continuous fossil record of at least 17.5 Ma. The stasis hypothesis is tested here as opposite to the possibility of a wider and previously non-identified specific diversity of Antarctic sparnotheriodontids. The material of N. arquinotensis available was compared in preservation, characters and dental occlusal areas to the more complete phylogenetic relative Sparnotheriodon epsilonoides and the North American Meniscotherium chamense. Despite there being no close phylogenetic relationship between Notiolofos and Meniscotherium, the morphological dental similarity between them suggests they could be interpreted as ecologically equivalent taxa. The analysis allows the reassignment of some N. arquinotensis teeth to other dental loci. The results indicate that there are no reasons to justify the presence of different species through the stratigraphic sequence or to refute the morphological stasis in N. arquinotensis. Stasis among Antarctic Eocene vertebrates is also recorded among Eocene penguins. The "Plus ça change" model indicate that morphological stasis and punctuated equilibrium were detected as the usual responses to widely fluctuating physical environments such as those characteristic of temperate regions and shallow waters. This model fits well with inferences on Antarctic paleoclimate and paleogeography and the land fossil record. Fil: Gelfo, Javier Nicolás. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina